STRATEGI PENINGKATAN DAN PENJUALAN PUPUK UREA BERDASARKAN TINGKAT KEPUASAN PELANGGAN DENGAN PENDEKATAN SERVQUAL DAN QFD - Wafiyatul Hidayah; Erni Puspanantasari Putri (Universitas Muhammadiyah Gresik, 2021)
Petrokimia Gresik is a subsidiary of PT. Pupuk Indonesia which produces fertilizer in support of the Government's Program to Increase Agricultural Production and National Food Security. In one of the Work Units, namely the Administration and Sales Department, there is one Fertilizer that rarely has income that does not meet the Company's RKAP Quantum Target, namely Urea fertilizer as evidenced by the Pre-Research results, Quantum Data Realization and Quantum Target RKAP Urea Fertilizer in 2021. In the research This analysis is carried out by analyzing customer perceptions and expectations using the Servqual Method to Measure Service Quality of the Urea Fertilizer Sales and Administration Department. Measurement results in finding the gap between Customer Perceptions and expectations from Servqual will be corrected with QFD. Then do the preparation of strategies that are applied to the Company. The results of Servqual show that all dimensions have a